2021
DOI: 10.1002/qj.4039
|View full text |Cite
|
Sign up to set email alerts
|

Forcing mechanism of the Silk Road pattern and the sensitivity of Rossby‐wave source hotspots to mean‐state winds

Abstract: The Silk Road pattern (SRP) is a leading mode of Eurasian atmospheric variability in boreal summer. It remains challenging for many models to predict the temporal phase of the SRP. This study investigates whether the forcing mechanism of the SRP can explain SRP prediction difficulty. Rossby‐wave sources (RWS) associated with the SRP are first identified in a reanalysis. An idealised barotropic model is then used to test wave propagation from all identified RWS, to isolate the relevant forcing locations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Our findings are only based on the MPI-GE data set, which contains model biases (Giorgetta et al, 2013;Hagemann et al, 2013;Müller et al, 2018) . It has been shown that model wind biases can alter the propagation of Rossby waves induced by North Atlantic SSTAs (Li et al, 2021) , which are relevant for modulating the atmospheric state and triggering heatwaves (Cassou et al, 2005;Kornhuber et al, 2020;Wulff et al, 2017) . Although it has been demonstrated that the low resolution version of the MPI model represents well the connection between spring North Atlantic SSTA and Eurasian surface temperatures via atmospheric wave trains (Chen et al, 2021), the availability of other large ensembles with high temporal frequency and spatial resolution would aid to verify our results.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are only based on the MPI-GE data set, which contains model biases (Giorgetta et al, 2013;Hagemann et al, 2013;Müller et al, 2018) . It has been shown that model wind biases can alter the propagation of Rossby waves induced by North Atlantic SSTAs (Li et al, 2021) , which are relevant for modulating the atmospheric state and triggering heatwaves (Cassou et al, 2005;Kornhuber et al, 2020;Wulff et al, 2017) . Although it has been demonstrated that the low resolution version of the MPI model represents well the connection between spring North Atlantic SSTA and Eurasian surface temperatures via atmospheric wave trains (Chen et al, 2021), the availability of other large ensembles with high temporal frequency and spatial resolution would aid to verify our results.…”
Section: Resultsmentioning
confidence: 99%
“…However, we hereby show that both mechanisms (i.e., thermal and mechanical forcings) simultaneously contribute to the formation of IA in the ME. On one hand, we see a westward continuous background flow on the east side of the ZAG in summer due to the existence of an anticyclone on the east side of the Caspian Sea so‐called, Turkmenistan anticyclone ( TKA ) (Mofidi & Zarrin, 2012), or Caspian Sea High (Kaskaoutis et al., 2016, 2017; Li et al., 2021; Y. Li et al., 2021) (Figure 3a). On the other hand, considering the diabatic heating equation (Q), we see significant values of negative vertical advection ()ωθp $\left(-\omega \frac{\partial \theta }{\partial p}\right)$ (about 2 K/day) from the top of the ZAG to the middle troposphere (Figures 3b and 3c).…”
Section: Resultsmentioning
confidence: 99%
“…For the proposed formation mechanism, the TKA and AA in the Aral Sea region and the eastern Mediterranean area are known as the Rossby‐wave source region. These two regional pressure systems generate such circulation by producing a waveguide through the Asian jet, which is called the Silk Road pattern (Ding & Wang, 2005; Enomoto, 2004; Enomoto et al., 2003; Li et al., 2021; Y. Li et al., 2021). In addition, TKA is also recognized to generate a quasi‐stationary mid‐tropospheric trough over the Caucasus during the summer by blocking the westerlies (Mofidi, 2007).…”
Section: Discussionmentioning
confidence: 99%